Variability of N2-fixation in common bean (Phaseolus vulgaris L.) under P deficiency is related to P use efficiency - Vadez, Vincent; Lasso, JH; Beck, Douglas P.; Drevon, J.J. (Springer, 1999)
Common bean often faces P deficiency in soils where it is generally grown. Such a deficiency is a major limitation to grain yield improvement, especially when common bean relies on N2 fixation. Screening for symbiotic N2 fixation (SNF) under P deficiency (72 ?mol P plant-1 week-1) was performed in a glasshouse with 220 lines originating from the Andean and Meso-American gene pools. Large variability in shoot dry weight and SNF under P deficiency was found. SNF tolerance to P deficiency was mostly found among late flowering type IV lines, with the exception of three early flowering type III lines. The SNF tolerance to P deficiency was correlated with: (i) low nodule P concentration in all the growth types, and (ii) intense and early nodulation for type IV lines, or (iii) large root dry weight and high nodule nitrogenase for type III lines. Large genotypic variability for nitrogen use efficiency, i.e. biomass per N concentration was also found. However, the ratio plant N per plant P concentration was the most discriminating. We concluded that this later ratio, which is almost similar to plant N-fixed per plant P concentration, in glasshouse hydroponics culture might be: (i) an estimate of the P use efficiency for SNF, (ii) a consequence of low P concentration in plant organs, especially nodules, and (iii) a determinant of genotypic variability of SNF tolerance to P deficiency.